The effect of humic preparations on the yield of oat fodder on permafrost soils of Yakutia - Osipova V.V.; Platonova A.Z.; Olesova M.M. (BIO Web of Conferences)
The livestock industry of the Republic of Sakha (Yakutia), being the main focus of agriculture, is experiencing an acute shortage of high-quality, protein-balanced feeds. The main reason for this is the reduction of areas under forage crops, the decline in agricultural production after the liquidation of large agricultural enterprises (state farms, collective farms) and, as a result, an increase in the volume of degraded, abandoned agricultural territories, and therefore, today agricultural producers of the republic face the urgent task of restoring lands with a low humus content by using all possible sources of fertilizers, including non-traditional resources. Under the conditions of permafrost meadow alluvial soils of the Republic of Sakha (Yakutia), studies were conducted to study the effect of humic preparations on the growth and development of oats cultivated for forage productivity. The biological products Agrolan, Lignohumate, and Normat L were studied in crops of oat of the Rovesnik variety, where plant treatment was carried out in the tube phase. Experiments have shown that leaf treatment of oat plants with Normat L, a natural growth stimulant and antistressant, causes intensive development of the leaf surface (110.4 cm2/plant), an increase in the foliage of oat plants (39.8%), and an increase in the forage mass of plants (12.2 t/ha). Obtaining high results when using the Normat L preparation is justified by its positive effect in case of soil and air drought over the years of experiments. The use of Lignohumat preparation, a plant growth stimulant and antistressant, contributes to achieving a relatively high feed weight yield of oat (11.0 t/ha). The use of the Agrolan preparation in forage crops is applicable in case of damage to plants by pests.